The Influence Perception of Privacy on Ambient Light Condition: Stimuli Affective Experiment - Pornchai Tamthinthai; Nopadon Sahachaisaeree (My University, 2012)
The environmental physical affects perception of visualization is based on the Gestalt. Perception of privacy is influenced by the configuration of the space in accordance with the person's past experiences. This research aims to find the relationship between the ambient lighting conditions with the perception of privacy, hypothesizing that the process perceives through the different types of people and factor. the research tool utilizes a set of 3D pictorial stimuli together with a questionnaire self-report and a semantic differential method to solicit response from subjects. The data to analysis of the statistically by software packages for social science research.
Keywords: Semantic differential; Public Spaces through Art